2017
DOI: 10.1016/j.respol.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Show me the Money: Federal R&D Support for Academic Chemistry, 1990–2009

Abstract: The research reported here was supported in part by the National Science Foundation's Science of Science and Innovation Policy Program under award 1064218. We have benefited from the insightful comments of Irwin Feller, David Popp, Otavio Bartalotti, participants in the Iowa State University "no free lunch" colloquium and several anonymous referees. We wish to express our appreciation for their assistance. Needless to say, any remaining errors are the responsibility of the authors. The views expressed herein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In addition, the number of R&D personnel also has a significant impact on innovation outputs. Rosenbloom [15] studied the relationship between the federal R&D funding received by industry-academia research groups in the United States and the number of postdoctoral personnel employed, and found a significant positive correlation between the two, which means the larger number of postdoctoral researchers leads to more research funding and thus increased innovation output. The internal culture or environment of an enterprise, including organizational structure, working culture and ad-ministrative processes, will affect its innovation.…”
Section: Enterprise Factor Inputmentioning
confidence: 99%
“…In addition, the number of R&D personnel also has a significant impact on innovation outputs. Rosenbloom [15] studied the relationship between the federal R&D funding received by industry-academia research groups in the United States and the number of postdoctoral personnel employed, and found a significant positive correlation between the two, which means the larger number of postdoctoral researchers leads to more research funding and thus increased innovation output. The internal culture or environment of an enterprise, including organizational structure, working culture and ad-ministrative processes, will affect its innovation.…”
Section: Enterprise Factor Inputmentioning
confidence: 99%
“…The core independent variables are government support (GST) and its quadratic term (GST2). As mentioned above, fiscal expenditure is the most basic way for local governments to support regional innovative activities [21]. It is reasonable to use government fiscal expenditure to reflect government support for university-enterprise knowledge flow [33].…”
Section: Dependent Variablesmentioning
confidence: 99%
“…We divided university-enterprise knowledge flow into dual stages, namely, knowledge creation and knowledge transfer, which further promote the research progress of university-enterprise cooperation in the field of knowledge management. Second, while many studies have shown that government support has a significant impact on university innovation performance or enterprise innovation ability [16,21], there is no unified answer as to whether local government behavior can play a role in university-enterprise cooperation. We found heterogeneous effects of government support on university-enterprise knowledge creation and knowledge transfer.…”
Section: Introductionmentioning
confidence: 99%